Drug prescription for the management of gastrointestinal and skin symptoms in cancer patients by advanced practice nurses in China: a Delphi method - Dan Zhou; Junying Li; Zhiying Yue; Mingli Zeng; Rujun Zheng (BMJ Open)
Background The authority to prescribe drugs has been reserved only for the medical community, mainly clinicians. Recently, more and more countries worldwide have begun implementing reforms to grant advanced practice nurses (APNs) the authority to prescribe from the legislative level. This study aimed to explore the prescription drugs and forms for gastrointestinal and dermatological symptom management of cancer patients that APNs can prescribe in China.Design A qualitative study reported in accordance with Conducting and REporting of DElphi Studies guidelines. The modified Delphi technique with two-round email consultations among 36 experts was applied.Methods We conducted a study from January 2022 to March 2022 to reach a consensus among medical, nursing and pharmacy experts about drugs that nurses may prescribe for gastrointestinal and dermatological symptom management in cancer patients.Results The expert authority coefficients are 0.95 and 0.96, respectively. A total of 35 drugs in 16 categories could be prescribed by APNs for gastrointestinal and dermatological symptoms management in China. Among them, three drugs were determined to be prescribed collaboratively, and 32 drugs were determined to be prescribed independently.Conclusions The drug prescription formulated in this study is the basis for APNs to prescribe drugs for controlling gastrointestinal and skin symptoms for cancer patients in mainland China. The results are important as a guide for formulating and implementing policies related to nurse prescribing and will provide some reference for future nurse prescribing in China.